Impact of The Covid-19 Pandemic On Law Enforcement of Violations For Violati Ons of Public Obligations In The City of Denpasar - I Ketut Sukadana; Ni Made Sukaryati Karma; I Nyoman Sutama (Eduvest - Journal of Universal Studies, 2022)
The purpose of this study is to examine and understand violations of public order during the covid-19 pandemic and to find policies carried out in law enforcement against violators. The economic impact of the COVID-19 pandemic has been felt by the community. People try to make a living with various businesses such as selling by choosing strategic locations on the roadside. Selling on the roadside, if it is associated with existing regulations, can be subject to sanctions for violating public order. The research method is carried out with the type of empirical legal research, with data collection techniques through interviews and recording. Based on the results of the study, during the Covid-19 period which had a very broad impact on the lives of residents, many people lost their source of livelihood because their workplace was unable to operate. In order to make a living, many people end up selling various kinds of merchandise on the side of the road. In Denpasar City, selling cars on the side of the road is prohibited in accordance with the provisions of Article 22 paragraph (1) of Denpasar City Regional Regulation Number 1 of 2015 concerning Public Order. The maximum penalty is 3 (three) months in prison or a maximum fine of Rp. 25,000,000, - (twenty five million rupiah) as stipulated in the provisions of Article 60 paragraph (2) of Denpasar City Regulation Number 1 of 2015. Law enforcement against violators cannot be carried out optimally because there is a special policy from the Mayor during the period of the pandemic is pursued in persuasive ways and emphasizes humanitarian considerations